Dispersion polymerization of styrene in supercritical carbon dioxide using monofunctional perfluoropolyether and silicone-containing fluoroacrylate stabilizers - Baran, N; Deniz, S; Akgün, M; Uzun, IN; Dinçer, S (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The free radical dispersion polymerization of styrene was carried out in supercritical carbon dioxide (scCO(2)) using two different stabilizers. The polymerizations are performed in the presence of poly(heptadecafluorodecyl acrylate-co-tris(trimethylsilyloxy)silyllpropyl methacrylate) p(HDFDA-co-SiMA) and a commercially available carboxylic acid-terminated perflouropolyether (Krytox (R) 157FSL) as polymerization stabilizers. Dry, fine powdered spherical polystyrene particles were produced under optimised conditions. The resulting high yield of spherical and relatively uniform micron-size polystyrene particles were formed utilizing various amounts of p(HDFDA-co-SiMA) random copolymer. However, it was observed that Krytox (R) 157FSL was not a good stabilizer as p(HDFDA-co-SiMA) for the dispersion polymerization of styrene. The particle diameter was shown to be dependent on the type of the stabilizer and the weight percent of the stabilizer added to the system. The effect of varying the concentrations of stabilizers and initiator, reaction time and reaction pressure upon the polymerization yield, molar mass and morphology of polystyrene have been investigated. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: dispersion polymerization; supercritical CO2; polystyrene particles; stabilizer; SILOXANE-BASED MACROMONOMER; SIZE POLYSTYRENE PARTICLES; PSEUDO-GRAFT STABILIZER; METHYL-METHACRYLATE; GLYCIDYL METHACRYLATE; CO2; COPOLYMERIZATION; REGIME; Polymer Science